The Influence of Work Conflict on Employee Performance at Bhayangkara Sartika Asih Bandung Hospital - Jaksa, Suherman (Dinasti International Journal of Management Science, 2024)
In this study the method used is descriptive and with a quantitative approach. The sampling technique used in this study is the Slovin formula technique with a sample size of 84 people from the total population of 510 employees. This study aims to determine whether work conflict can significantly affect employee performance, both positively and negatively. The method used is a survey with a questionnaire using a questionnaire as a data collection instrument. The sample of this study amounted to 84 respondents, namely employees who work at Bhayangkara Sartika Asih Bandung Hospital. The data collected will be analyzed using descriptive statistical methods and regression analysis. This research consists of four main stages. The first stage is primary data collection through a questionnaire distributed through Google Form to employees at the hospital. This questionnaire includes variables related to work conflict and employee performance. The second stage is data processing, where the collected data will be analyzed using descriptive statistical methods to get an overview of the level of work conflict and employee performance in the hospital. Furthermore, regression analysis will be conducted to examine the relationship between work conflict and employee performance. The third stage is the interpretation of the analysis results, where the findings from the data analysis will be explained and analyzed in depth. These results will provide a better understanding of the relationship between work conflict and employee performance at Bhayangkara Sartika Asih Bandung Hospital. The final stage is the preparation of the research report, in which the findings and recommendations will be presented in a systematic and comprehensive manner. The results of this study are expected to provide a better understanding of the relationship between work conflict and employee performance in the hospital. In addition, this research is also expected to provide recommendations to hospital management in managing work conflict in order to improve employee performance.